Peri-Urban Land Transformation in the Global South: Revisiting Conceptual Vectors and Theoretical Perspectives - Shiwaye M. Tesfay; Genet Alem Gebregiorgis; Daniel G. Ayele (Land)
Peri-urban areas in the Global South are rapidly transforming due to urban expansion, land commodification, and institutional change. Although diverse theoretical perspectives address these dynamics, existing scholarship remains fragmented. This study systematically reviews how various theoretical frameworks deepen our understanding of peri-urban land transformation, focusing on conceptual and institutional dimensions. Following PRISMA 2020 guidelines, a systematic review was conducted on 120 studies published between 1996 and 2024, sourced from Scopus, Web of Science, ProQuest, and additional unindexed repositories. Eligible studies explicitly addressed peri-urban land issues in the Global South and applied theoretical approaches. Data extraction involved detailed coding of study characteristics, theoretical orientations, and thematic insights. Using open and selective coding, 19 thematic codes were identified. Three overarching themes emerged: (1) conceptualizing peri-urban spaces through territorial, functional, and transitional lenses; (2) institutionalization of place; and (3) theoretical interpretations of land transformation grounded in neoclassical, modernization, neo-Marxist, dependency, structuration, institutionalist, and urban political ecology frameworks. Studies were appraised for theoretical rigor, relevance, and potential conceptual bias. Limitations include the exclusion of non-English studies. Findings highlight the need for pluralistic, context-sensitive frameworks, with political ecology offering a particularly integrative analytical lens to examine global–local power dynamics and socio-natural transformations. This review was funded by the Alexander von Humboldt Foundation (Georg Forster Fellowship, grant no. 1233452).